Effects of increased nurses' workload on quality documentation of patient information at selected Primary Health Care facilities in Vhembe District, Limpopo Province - Rhulani C. Shihundla; Rachel T. Lebese; Maria S. Maputle (AOSIS, 2016)
Background: Recording of information on multiple documents increases professional nurses' responsibilities and workload during working hours. There are multiple registers and books at Primary Health Care (PHC) facilities in which a patient's information is to be recorded for different services during a visit to a health professional. Antenatal patients coming for the first visit must be recorded in the following documents: tick register; Prevention of Mother-ToChild Transmission (PMTCT) register; consent form for HIV and AIDS testing; HIV Counselling and Testing (HCT) register (if tested positive for HIV and AIDS then this must be recorded in the Antiretroviral Therapy (ART) wellness register); ART file with an accompanying single file, completion of which is time-consuming; tuberculosis (TB) suspects register; blood specimen register; maternity case record book and Basic Antenatal Care (BANC) checklist. Nurses forget to record information in some documents which leads to the omission of important data. Omitting information might lead to mismanagement of patients. Some of the documents have incomplete and inaccurate information. As PHC facilities in Vhembe District render twenty four hour services through a call system, the same nurses are expected to resume duty at 07:00 the following morning. They are expected to work effectively and when tired a nurse may record illegible information which may cause problems when the document is retrieved by the next person for continuity of care. Objectives: The objective of this study was to investigate and describe the effects of increased nurses' workload on quality documentation of patient information at PHC facilities in Vhembe District, Limpopo Province. Methods: The study was conducted in Vhembe District, Limpopo Province, where the effects of increased nurses' workload on quality documentation of information is currently experienced. The research design was explorative, descriptive and contextual in nature. The population consisted of all nurses who work at PHC facilities in Vhembe District. Purposive sampling was used to select nurses and three professional nurses were sampled from each PHC facility. An in-depth face-to-face interview was used to collect data using an interview guide. Results: PHC facilities encountered several effects due to increased nurses' workload where incomplete patient information is documented. Unavailability of patient information was observed, whilst some documented information was found to be illegible, inaccurate and incomplete. Conclusion: Documentation of information at PHC facilities is an evidence of effective communication amongst professional nurses. There should always be active follow-up and mentoring of the nurses' documentation to ensure that information is accurately and fully documented in their respective facilities. Nurses find it difficult to cope with the increased workload associated with documenting patient information on the multiple records that are utilized at PHC facilities, leading to incomplete information. The number of nurses at facilities should be increased to reduce the increased workload. Keywords: Effects; increased; professional nurses'; work-load; quality nursing documentation; patient information